Emergence of the Nepali Nation-State: A Stepping Stone to Modernity - Thapa, Bal Bahadur (Pragya Darshan प्रज्ञा दर्शन, 2023)
The present qualitative study examines Prithvi Narayan Shah’s Dibya Upadesh in the light of relevant historical details and thereby makes a claim that his venture of unification led to the rise of nascent nation-state, which became Nepal’s stepping stone to modernity. In connection to the ideas related to nation-state, capitalism and modernity, this study engages with the ideas of Anthony Giddens, Benedict Anderson, Ernest Renan, Mark Leichty, Mahesh Chandra Regmi, among others.